(untitled) - Spiller, Elizabeth (Cambridge, UK, 2004)
This monograph documents the development of two cultures and disciplines: science and literature--through a shared aesthetic of knowledge. It brings together key works in early modern science and imaginative literature, ranging from the anatomy of William Harvey and the experimentalism of William Gilbert to the fiction of Philip Sidney, Edmund Spenser and Margaret Cavendish.
Keywords: Science in literature,Renaissance,Văn chương Anh Quốc,English literature,Thời kỳ phục hưng; History and criticism; Early modern, 1500-1700; England,Anh quốc